Consumer Perception on Influencer Marketing Efforts of Brands in the Beauty and Cosmetics Industry - Abraham, John Simon E; Floreto, Sophia Justine L.; Pagkalinawan, Margaux Isabella B.; Etrata, Antonio E. (IJOSMAS, 2022)
The study targets to address the gaps on insufficient research on the shift from traditional marketing trends and current marketing trends in the Philippines, specifically influencer marketing on various digital media platforms present today. For the benefit of cosmetic companies, marketing agencies, and future researchers as a basis for future campaigns or research in line with influencer marketing, this research aims to determine significant factors affecting the perception (purchase intention and recommendation) of consumers in the beauty and cosmetics industry, specifically the following: sponsorship disclosure labels, platforms used, type of post, and credibility of influencers. Following a descriptive-correlational approach, a pool of two hundred twenty-six (226) respondents were surveyed. A Structural Equation Model (SEM) was used to measure their perception towards influencer marketing along with their overall sentiments towards the identified factors. The results of the study revealed that type of post plays a major factor in perception towards and interest in brands. Aside from the type of post, the influencers themselves play a major role in determining the purchase intention and recommendation that respondents have towards brands. However, for type of post and sponsorship disclosure labels, results show that these do not have a significance on the perceptions of consumers in terms of purchase intention and recommendation.